Recent progress of SPAN towards neutrino mass spectroscopy. Issue 6 (May 2016) - Masuda, T; Hara, H; Miyamoto, Y; Sasao, N; Tanaka, M; Uetake, S; Yoshimi, A; Yoshimura, K; Yoshimura, M
Abstract: SPAN (Spectroscopy of Atomic Neutrino) project aims to determine the absolute neutrino mass. The process we plan to use is a cooperative de-excitation of atoms in a metastable level emitting a neutrino pair associated with a photon. The photon energy spectrum of this process contains information on the absolute mass of neutrino. Key items of this experiment are a rate amplification using macro-coherence in a target medium in case of plural particles emission and an external triggering of the emission in order to scan the spectrum. We have demonstrated the rate amplification in two-photon emission from para-hydrogen gas which was coherently excited to its first vibrationally excited state. The coherence in the medium was generated by irradiating two driving laser pulses. The emission was stimulated by irradiating a mid-infrared laser pulse. The enhancement factor of more than 10 18 with respect to the spontaneous emission was achieved. This paper briefly summarizes the results.